find the value of k if 2x+1 is a factor of (3k+2)x^3+(k-2)
Answers
Answered by
1
Step-by-step explanation:
2x+1 is a factor
2x+1=0
x=-1/2
(3k+2)x^3+(k-2)
(3k+2)(-1/2)^3+(k-2)=0
(3k-2)(-1/8)+(k-2)=0
-3k/8+k+1/4-2=0
5k/8-7/8=0
5k/8=7/8
k =7/5
Answered by
5
Answer:
We'll use the factor theorem here.
____________________________.
____________________________.
Putting in the value of x in p(x)
(We put the value 0 because we know that 2x+1 is a factor of p(x) and it's remainder will obviously be 0 considering the given information)
_____________________________.
Similar questions
Math,
2 months ago
Math,
2 months ago
Math,
4 months ago
Business Studies,
4 months ago
English,
11 months ago
Accountancy,
11 months ago